Early Mobility and Rehabilitation Protocol after Internal Brace Ankle Stabilization - Bryanna Vesely; Shanthan Challa; Benjamin Moyer; Blake Gereb; Troy Watson (International Journal of Sports Physical Therapy)
Chronic lateral ankle instability is a common diagnosis in foot and ankle clinics. Internal Brace (IB) augmentation is a surgical procedure that utilizes fibertape augmentation of the lateral ankle ligaments. Studies have shown the superiority of fibertape augmentation over traditional lateral ankle stabilization procedures such as the Brostrom or Brostrom-Gould. The IB procedure has been described elsewhere and the fixation involves placing bone anchors with attached suture tape at each end of the Brostrom repair augmenting the fixation. Various studies exist that support the mechanical advantage of the Brostrom with IB over non augmented repair. This technique allows for earlier weight bearing and range of motion which translates into earlier return to activity and sport. While there are guidelines for rehabilitation after Brostrom procedures, there are currently no guidelines regarding rehabilitation after the IB. The purpose of this clinical commentary is to describe an early mobility and rehabilitation protocol after IB augmentation for the ankle. The post operative protocol provides treatment goals, weight bearing status recommendations, and rehabilitation intervention suggestions after IB augmentation.